VITREORETINAL DISEASES IN OUTPATIENT DEPARTMENT OF BALI MANDARA EYE HOSPITAL IN 2019 - Ni Made Tyas Dwi Arshanti; Ni Luh Diah Pantjawati; I Ketut Semara Budiyasa; Cindy Hartono (International Journal of Retina, 2022)
Introduction: The purpose of this study is to identify the pattern and distribution of vitreoretinal (VR) diseases in Bali Mandara Eye Hospital Methods: A retrospective descriptive study was conducted for this study. We reviewed all medical records of new patient diagnosed with VR diseases, from 1 January to 31 December 2019. We recorded and measured demography, history of systemic and eye disease, symptoms and onset, ophthalmic examinations, diagnostic investigations, final diagnoses, therapies, and the completion of the visit. Results: Out of 2118 total visits, we found 1191 new cases with VR diagnosis. The male to female ratio was 1.3:1. We found a group of 46-65 years is represented in 678 cases (56.9%). Type 2 diabetes mellitus was the most commonly found as a systemic disease (15.5%), followed by the combination of diabetes and hypertension (14%) and hypertension alone (12.9%). History of previous cataract surgery was found in 174 cases (14.6%). Out of 1191 patients, 553 patients (46.4%) were blind. The most common diagnosis was diabetic retinopathy (19.7%), followed by rhegmatogenous retinal detachment (10.8%), and vitreous opacity (9.9%). Diabetic retinopathy affected both eyes in 302 cases (89.6%), while rhegmatogenous retinal detachment and vitreous opacity commonly affected one eye in 177 cases (95%) and 123 cases (73%), respectively. Proliferative diabetic retinopathy was found in 171 cases (50.7%). Conclusions: Diabetic retinopathy and rhegmatogenous retinal detachment were the most two common diagnoses. The proliferative type was slightly common than Non-Proliferative Diabetic Retinopathy. As diabetes and hypertension were the most systemic conditions we found, a collaboration with another department is needed to create a strategic screening system and early detection. An evaluation related to rhegmatogenous retinal detachment is needed to decrease the number of cases.